Aromaterapi Lavender dan Audio Hipnosis Terhadap Penurunan Kecemasan Menghadapi Persalinan pada Ibu Hamil Trimester III: (Literatur Review) - Nurfajriah, Suci; Atnesia Ajeng; Ika Oktaviani; Puspitasari Budiyanti (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
Data from the World Health Organization (WHO) in 2020 shows that around 8-10% experi- ence anxiety during pregnancy and this increases to 13% when delivery ap- proaches. Midwives have a big role in overcoming this problem, one of which is by lavender aromatherapy and audio hypnosis. Research objective: to determine of giving lavender aromatherapy and audiohypnosis to reduce anxiety facing child- birth in third trimester pregnant women. Researchmethodology: Search for jour- nals using a database via Google Schoolar and Pubmed with keywords, then 10 journals were found that met the inclusion and exclusion criteria which were then reviewed. The research results from each journal show that the intervention of providing lavender aromatherapy and audio hypnosis has an effect on reducing anxiety facing childbirth in third trimester pregnant women. Conclusion: The intervention of providing lavender aromatherapy and audio hypnosis has an effect on reducing anxiety facing childbirth in third trimester pregnant women. Suggestion:Pregnant women who receive of lavender aromatherapy and audio hypnosis inter- vention are expected to be able to carry out the intervention correctly so that they can overcome stress and tension during pregnancy.